PENGEMBANGAN ATLAS TANAMAN OBAT DI DESA KAMPUNG BARUH KECAMATAN TABIR KABUPATEN MERANGIN SEBAGAI BAHAN AJAR SISWA DI SMK - Dina Wulandari; Rodiantifitri Nengsih; Leni Marlina (Pendidikan Biologi STKIP YPM Bangko, 2020)
This research is motivated by the lack of teaching materials such as books limited student handbook. In addition, the display of teaching materials what is available is less attractive, the language is difficult to understand, minimal pictures. To to overcome this, the researchers developed the Atlas of medicinal plants as ingredients teach students at SMK. This study aims to describe the process development of Atlas of medicinal plants as teaching materials in the material biodiversity for class X SMK and to produce an Atlas valid. This type of research is a development research using the 4-D Model which includes the stage of define, design, develop, and disseminate. The subject this study consisted of 7 validators. Based on the result of this study the resulting product is a medicinal plant Atlas. Atlas of medicinal plants produced declared very valid by the validator both from the aspects of content feasibility, language, presentation, and graphics with a validity value of 89%. It can be concluded that the Atlas of medicinal plants has been declared valid.